Silencing of miR-483-5p alleviates postmenopausal osteoporosis by targeting SATB2 and PI3K/AKT pathway - Fujiang Zhao; Yier Xu; Yulong Ouyang; Zhexu Wen; Guihao Zheng; Ting Wan; Guicai Sun (2021)
Postmenopausal osteoporosis (PMOP) poses a significant threat to women's health worldwide. However, detailed molecular mechanism and therapeutic strategy for PMOP remain insufficient. Accumulating evidence suggests that miR-48-5p is implicated in the pathogenesis of osteoporosis. The present study aimed to determine the role and mechanism of miR-483-5p in PMOP. Results from PMOP patients demonstrated that miR-483-5p was up-regulated and SATB2 was down-regulated. Luciferase reporter assay identified SATB2 as a direct target gene of miR-483-5p. Experiments in MC3T3-E1 cells indicated that miR-483-5p mimic markedly inhibited cell viability as well as the expressions of OPG, RUNX2 and BMP2. And miR-483-5p inhibitor, SATB2-overexpressed lentiviruses (Lv-SATB2) or LY294002 (PI3K/AKT inhibitor) significantly reversed the above results. Similarly, PI3K/AKT signaling was activated by miR-483-5p mimic, and was inhibited in miR-483-5p inhibitor, Lv-SATB2 or LY294002 treated cells.